NEUROLINGUISTIC STUDY OF VERBAL COMMUNICATION (American Journal of Business Management, Economics and Banking, 2022)
The article aims to introduce the basic rules and functions of neurolinguistics, the history of this field, specific neurolinguistic research, methodology and scientific paradigms, language and communication, thinking, neurophysiological processes.